SCJD Exam with J2SE 5 - Monkhouse, Andrew; Camerlengo, Terry; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
You already know how crucial certification is within the Java community. SCJD Exam with J2SE 5, Second Edition is a valuable guide to prepare for the exam. This book has been updated for the Java version J2SE 5.0, and works its way through a project with requirements and structure similar to the project you'll encounter in the exam. Upon reading this book, you'll become intimately familiar with key concepts, challenges, and pitfalls that the exam is likely to test you on.
and General Development Considerations -- Project Analysis and Design -- Project Overview -- Implementing a J2SE Project -- Threading -- The DvdDatabase Class -- Networking with RMI -- Networking with Sockets -- The Graphical User Interfaces -- Wrap-Up -- Project Wrap-Up.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books